2012
DOI: 10.1039/c2cc37184g
|View full text |Cite
|
Sign up to set email alerts
|

Benzothiadiazole-containing donor–acceptor–acceptor type organic sensitizers for solar cells with ZnO photoanodes

Abstract: Dye-sensitized solar cells using nanocrystalline ZnO as the photoanode and a metal-free sensitizer with a benzothiadiazole entity directly connected to the 2-cyanoacrylic acid acceptor exhibited an efficiency (5.18%) higher than those using the TiO(2) photoanode. Use of a hierarchical ZnO back scattering layer further improved the efficiency to 5.82%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…The spectral range at lower energy shows a band in the visible region (400-575 nm), which can be assigned to the intramolecular charge transfer (ICT) that occurs between the electronwithdrawing and electron-donating parts of both dyes 8 and 9, respectively. [23,34] 8 and 9 present both broad bands up to ∼ 600 nm. Taking into account this broad absorption, quite high short-circuit photocurrent density (J sc ) can be expected.…”
Section: Synthesis and Characterizationmentioning
confidence: 97%
“…The spectral range at lower energy shows a band in the visible region (400-575 nm), which can be assigned to the intramolecular charge transfer (ICT) that occurs between the electronwithdrawing and electron-donating parts of both dyes 8 and 9, respectively. [23,34] 8 and 9 present both broad bands up to ∼ 600 nm. Taking into account this broad absorption, quite high short-circuit photocurrent density (J sc ) can be expected.…”
Section: Synthesis and Characterizationmentioning
confidence: 97%
“…[10][11][12][13] Various metal-free organic dyes with high absorption coefficients have been investigated as sensitizers of TiO 2 and ZnO DSSCs. [10][11][12][13][14][15][16] The good intramolecular charge transfer upon excitation is achieved by using D-p-A molecular structures, D being the donor group, A the acceptor group and p a long conjugated chain. 3 The anchoring group is localized in the vicinity of the acceptor group in order to favor the fast electronic charge transfer to the oxide after excitation.…”
mentioning
confidence: 99%
“…However, the efficiency was far from satisfactory, and the best photon-to-electricity conversion efficiency of the DSSCs reported only reached ∼70% of the standard cell based on cis -Ru­(NCS) 2 (dcbpy) (dcbpy = 2,2′-bipyridyl-4,4′-dicarboxylate). Later, we and others found that much improved efficiencies could be achieved with BT-based sensitizers after appropriate modification of the conjugated spacer. We and others also found that replacement of the BT unit by a less electron deficient benzotriazole (BTz) unit improved the power conversion efficiencies. Based on the D–A−π–A dyes developed in our group with different electron-deficient entities such as BT, , BTz, cyanovinyl entity, pyrido­[2,1,3]­thiadiazole and 2 H -[1,2,3]­triazolo­[4,5- c ]­pyridine, we found that the Mulliken charges of the second acceptor in the S 0 → S 1 transition was an useful semiempirical index for the electron injection efficiency of the dye molecule and the cell efficiency as well, that is, the cell efficiency drops as the Mulliken charge of electron-deficient entity goes more negative.…”
Section: Introductionmentioning
confidence: 99%